Enhancing the Delivery of Comprehensive Care for People Living with HIV in Canada - Wilson, MG; Mattison, CA; Gao, C; Kendall, CE; Lavis, JN (My University, 2019)
An assessment of what is known about problems related to enhancing the delivery of comprehensive care, options for addressing these problems, and key implementation considerations. The citizen brief was an input to a citizen panel on the topic of enhancing the delivery of comprehensive care for people living with HIV in Canada.
Keywords: delivery; comprehensive; care; human immunodeficiency virus; Canada